Looking at neonatal facial features of pain: do health and non-health professionals differ? - Juliana do Carmo Azevedo Soares; Marina Carvalho de Moraes Barros; Giselle Valério Teixeira da Silva; Lucas Pereira Carlini; Tatiany Marcondes Heiderich; Rafael Nobre Orsi; Rita de Cássia Xavier Balda; Pedro Augusto Santos Orona Silva; Carlos Eduardo Thomaz; Ruth Guinsburg (Jornal de Pediatria, 2022)
Objective: To analyze the regions that trigger the attention of adults’ gaze when assessing pain in newborn infants’ pictures and to verify if there are differences between health and non-health professionals. Method: Experimental study with 84 health professionals and 59 non-health professionals, who evaluated two images of 10 neonates, one at rest and the other during a painful procedure. Each image was shown for 7 seconds on a computer screen, while eye movements were tracked by the Tobii TX300 EyeTracker. After evaluating each image, participants gave a score from 0 (absent pain) to 10 (maximum pain), according to their perception of neonatal pain. For each image, the number and total time of gaze fixations in the forehead, eyes, nasolabial furrow, and mouth were studied. Comparisons between both groups of adults were made by an intraclass correlation coefficient, Student's t-test, and Bland Altman graphic. Results: Health professionals (93% female; 34 ± 9 years old), compared to non-health professionals (64% female; 35 ± 11 years old), gave lower scores for images at rest (0.81 ± 0.50 vs. 1.59 ± 0.76; p = 0.010), with no difference for those obtained during the painful procedure (6.98 ± 1.08 vs. 6.73 ± 0.82). There was a strong or almost perfect correlation for the number of fixations in the mouth, eyes, forehead, and for the total fixation time in the eyes and forehead. Conclusions: Adults, irrespective of their profession, showed a homogeneous gaze pattern when evaluating pictures of neonates at rest or during a painful procedures.